Three-dimensional finite element analysis of teeth displacement patterns under four anchorage designs for maxillary molar distalization using clear aligners: a real-case based simulation study - Huanhuan Chen; Wei Li; Chenda Meng; Yue Lai; Tianmin Xu; Bing Han; Guangying Song (BMC Oral Health)
Abstract Objective To explore the three-dimensional (3D) displacement patterns of maxillary molar distalization using clear aligners (CA) under four anchorage designs and provide clinical guidelines for optimal traction methods. Materials and methods A 3D finite element model was constructed based on CBCT and digital models from an adult patient requiring maxillary molar distalization. The model included cortical bone, cancellous bone, periodontal ligament, teeth, CA, and mini-screws. Four anchorage designs were simulated during sequential distal movement of bilateral maxillary second molars, first molars, and second premolars: (a) intramaxillary anchorage, (b) intermaxillary anchorage, (c) buccal mini-screw anchorage, and (d) palatal mini-screw anchorage. Displacement patterns of anterior and molar teeth were analyzed using ANSYS software and compared to the patient’s actual maxillary dentition movement. Results Most teeth’s actual displacement aligned with finite element predictions, except for central incisors, which showed mesial tipping instead of the simulated distal tipping. In the sequence-specific simulations: (1) Second molars only: All groups exhibited labial tipping and extrusion of anterior teeth (greater in Groups (a) and (b)), distal and buccal tipping with intrusion of second molars, and buccal tipping with extrusion of first molars (distal tipping in Groups (c) and (d), mesial in Groups (a) and (b)). (2) Second and first molars simultaneously: Anterior teeth showed reduced labial tipping, with palatal tipping and intrusion of right canines in Groups (c) and (d). All groups displayed distal tipping and intrusion of molars, with palatal tipping in second molars and buccal tipping in first molars. (3) Second premolars initiated: Anterior teeth in Groups (c) and (d) exhibited reduced labial tipping and extrusion, even with some palatal tipping and intrusion. Second molars in Groups (a) and (b) showed mesial, buccal tipping, and extrusion, while first molars in all groups and second molars in Groups (c) and (d) showed distal, palatal tipping, and intrusion. No significant differences in torque or vertical control were observed between buccal and palatal mini-screw anchorage. Conclusions Compared to intramaxillary or intermaxillary anchorage, the combination of mini-screws anchorage has a better effect on the torque control of anterior teeth, which also helps to promote the distal movement of molars. While no significant differences were observed in the torque and vertical control of anterior teeth or molars between buccal and palatal mini-screws, the findings underscore the versatility of mini-screw anchorage in accommodating individual patient anatomies. Notably, the displacement patterns of bilateral maxillary teeth were not always symmetrical, highlighting the need for personalized treatment planning and close monitoring during orthodontic therapy.